2020
DOI: 10.1101/2020.03.12.20034660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact assessment of non-pharmaceutical interventions against COVID-19 and influenza in Hong Kong: an observational study

Abstract: Background: A range of public health measures have been implemented to delay and reduce local transmission of COVID-19 in Hong Kong, and there have been major changes in behaviours of the general public. We examined the effect of these interventions and behavioral changes on the incidence of COVID-19 as well as on influenza virus infections which may share some aspects of transmission dynamics with COVID-19. Methods: We reviewed policy interventions and measured changes in population behaviours through two te… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 19 publications
1
85
1
4
Order By: Relevance
“…Recent ILI data for the United States show a markedly lower epidemic peak for the 2019-2020 influenza season compared to what would be expected based on the pre-holiday peak [8]. A similar phenomenon has been observed in other locations including Hong Kong and France [9,10]. Understanding this uncharacteristic ILI behavior is important for understanding influenza epidemiology and optimizing influenza mitigation e↵orts.…”
Section: Introductionmentioning
confidence: 81%
“…Recent ILI data for the United States show a markedly lower epidemic peak for the 2019-2020 influenza season compared to what would be expected based on the pre-holiday peak [8]. A similar phenomenon has been observed in other locations including Hong Kong and France [9,10]. Understanding this uncharacteristic ILI behavior is important for understanding influenza epidemiology and optimizing influenza mitigation e↵orts.…”
Section: Introductionmentioning
confidence: 81%
“…Attack rates were projected to be highest in those aged 5-14 years (77%, 95% CrI: 63-83%) and 15-49 years (63%, 95%CrI: 48-71). Lower attack rates were projected in individuals aged less than 5 years (50%, 95% CrI: 37-58%) and adults aged 50-69 years (47%, 95% CrI: 34-55) and greater than 70 years (30%, 95% CrI: [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]). An example of the outbreak trajectory across model simulations is presented in Figure 2.…”
Section: Base Casementioning
confidence: 99%
“…As such, population-level interventions, with their attendant economic costs, have been used to prevent health systems from collapsing (24). While events in China, Singapore, Hong Kong and elsewhere have demonstrated that COVID-19 epidemics can be contained (24)(25)(26)(27), the seeding of epidemics in countries around the globe, many with weak health systems (28), means that reintroduction of COVID-19 will continue to occur for some time. As successful containment efforts maintain a large number of susceptible individuals in populations, vulnerability to repeated epidemics is likely to persist until a COVID-19 vaccine is developed and manufactured at scale; or until large fractions of the population are infected and either die or develop immunity (29).…”
Section: Dynamic Interventionsmentioning
confidence: 99%
“…. DM tDR S DS) 1 S) p = ( − p * p ÷ ( − p Knowing the limitations of previous modelling attempts (Cowling et al;Ganyani et al, 2020;Zhang et al, 2020;Chen et al, 2020;Wu, Leung & Leung, 2020;Lin et al, 2020;Kucharski et al, 2020) , we decided to test a radically different COVID-19 epidemiologic paradigm, i.e. a significantly lower tDR .…”
Section: Model Parametrizationmentioning
confidence: 99%